How CEO Workaholism Influences Firm Performance: The Roles of Collective Organizational Engagement and TMT Power Distance - She, Zhuolin; Li, Quan; Zhou, Jilei (Frontiers in Psychology, 2021)
Based on upper echelons theory, the current study examines how and under what conditions CEO workaholism influences firm performance. Specifically, we propose that CEO workaholism is positively related to collective organizational engagement, which has a subsequent positive effect on firm performance. Top management team (TMT) power distance would moderate the relationship between CEO workaholism and collective organizational engagement in such a way that workaholic CEOs are more likely to stimulate collective organizational engagement when TMTs have a high level of power distance. Findings based on multi-source, multi-wave data from a sample of 122 CEOs and their corresponding TMT members supported the hypotheses. This study is an initial attempt to empirically examine the effects of leader workaholism at the firm level, which answers the call for more research into the intersection of workaholism and leadership and carries implications for organizational management practices.